Estudio comparativo del aceite esencial de Minthostachys mollis (Kunth) Griseb "Muña" de tres regiones peruanas por cromatografía de gases y espectrometría de masas - Fuertes Ruitón, César M. (2001)
A Study of the chemical composition of the essential oil of Minthostachys mollis (Kunth) Griseb, has been done by means of chromatographic and spectronic methods, in order to determine the composition according to the place of selling. We found the following: in the essential oil from Tarma (Junín, región A. A. Cáceres): l-tetradecene (23,14%), 2S-transmenthona (23,00%) and pulegone (13,21%), in the essential oil from Huaraz (Ancash. Región Chavín): 2S-trans-menthona (41,48%), pulegone (16,02%), y - terpinen (7,55%) and in case of essential oil from Pampas (Huancavelica, región Los Libertadores Wari): 2S-trans-menthona (34,51 %), pulegone (28,62%), and nerolidol (5,08%).